Improving Students’ Social Intelligence through the Sociodrama Method at Senior High School - Tatiek Handayani; Umar Umar; Sukarddin Sukarddin (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was backgrounded by observational data of students with low levels of social intelligence in class XI IIS SMAN 3 Sumbawa Besar. To respond to this, the author carried out quantitative descriptive research aimed at improving social intelligence through the application of the sociodrama method, while the purpose of the study was How effective the application of the sociodrama method was to increase the social intelligence of students at SMA N 3 Sumbawa Besar. The research method used is descriptive quantitative, using quasi-experimental design in the form of control group design. Data analysis in this study performed using SPSS version 22.0 by conducting a normality test first using the kolmogrov smirnov test with data collection techniques using questionnaires, observations and documentation. According to the descriptive analysis, the mean pre-and post-test scores were 104.91 and 121.87, respectively, and the mean percentage of student learning activity was 65.90%. This number demonstrates that students' social intelligence increases significantly after employing the sociodrama method. Changes in the attitude of students who concentrate more while studying, are neater, respect the opinions of others, are more creative and innovative, are more responsible, and talk appropriately and courteously indicate an increase in intelligence.